FINANCING TERTIARY EDUCATION: INTERNATIONAL AND HUNGARIAN EXAMPLES OF TUITION FEES - Keresztes, Eva Reka (European Scientific Journal, ESJ, 2014)
Tertiary education plays a very important role in the competitiveness of youth employment. The accumulation of human capital is not only beneficial to the individual, but to the sustainable knowledge economy. Parallel with the expansion of higher education, the average level of education has risen over the past decades across the OECD. However, governments in various part of the world have various approaches in financing tertiary education. Basically, there are four types of models which exist concerning the amount of tuition fees and the development of student support systems. In Hungary, the financing of higher education follows partly market modeling and partly cost modeling. Thus, this modeling was according to per capita funding formula on the grounds of the previous year’s per capita basis and agreements. Considering tuition fees, the offered feepaying programmes of the term 2014/2015 were analyzed according to 15 fields of study and three degree levels of education. Consequently, the amount of fees can be explained more by the resource-intensiveness and popularity of these programmes, but less by the labour-market opportunities.